Biological control of bacterial blight of rice: Attempts to induce resistance using bioagents - Tandon, Aishwarya; Thrimurty, V S; Khare, N (Indian Journal of Plant Protection, 2020)
Induced resistance and microbial antagonism were investigated as possible methods for control of bacterial blight (BB) of rice caused by Xanthomonas oryzae pv. oryzae. Response of resistance genes identified against BB was studied under Chhattisgarh condition on genotype IRBB-59 (possessing three resistance genes i.e. Xa 5 + xa 13 + Xa 21). Seventy two hours before inoculation treatments were applied by thoroughly mixing the specific solution of bioagents (approximately 108 cfu ml-1) and sprayed on the foliage of the plants with the help of atomizer. After 72 hours of treatment application, first four leaves from the top were pathogen inoculated by clip inoculation. Treatment with the bioagents showed significant reduction in disease severity, particularly plants were challenged by clip inoculation. The result showed that Pseudomonas fluorescens sprayed @ 3g/l. superiorly reduced the disease severity over control and at par with Bacillus subtilis @ 3g/l. Spraying of P. fluorescens 3g/l. significantly increased the bundle weight over control. However, it was at par with P. fluorescens 2g/l and B. subtilis 3g/l.